2019
DOI: 10.1021/acs.jpcc.9b02158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of External Electric Field on Poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-co-(bithiophene)] Chain Orderness, Morphology, and Carrier Mobility in Different Condensation Processes

Abstract: Poly[(9,-alt-co-(bithiophene)] (F8T2) is a kind of crystal and liquid-crystal conjugated polymer (CP). In this research, the effect of external electric field (EEF) on F8T2 chain orderness, morphology, and carrier mobility in different condensation processes of annealing at 130 °C (above glass-transition temperature), 200 °C (crystallization temperature), and 280 °C (liquid-crystal temperature) was investigated by UV−vis absorption spectroscopy, photoluminescence spectroscopy, Xray diffraction, atomic force mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…However, the EEF increased the mobility of the 100% P3HT film from 0.73 × 10 –3 to 2.69 × 10 –3 cm 2 V –1 s –1 , and the growth rate was 268%. This result was consistent with the increasing trend of chain orderness in the films, indicating that charge transport in the P3HT films strongly depended on the chain-ordered structure that provided an efficient channel for charge transfer . Notably, the mobility of the PTB7/P3HT blended film (with 30% P3HT) increased from 2.72 × 10 –3 to 6.76 × 10 –3 cm 2 V –1 s –1 with the application of the EEF.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…However, the EEF increased the mobility of the 100% P3HT film from 0.73 × 10 –3 to 2.69 × 10 –3 cm 2 V –1 s –1 , and the growth rate was 268%. This result was consistent with the increasing trend of chain orderness in the films, indicating that charge transport in the P3HT films strongly depended on the chain-ordered structure that provided an efficient channel for charge transfer . Notably, the mobility of the PTB7/P3HT blended film (with 30% P3HT) increased from 2.72 × 10 –3 to 6.76 × 10 –3 cm 2 V –1 s –1 with the application of the EEF.…”
Section: Resultssupporting
confidence: 80%
“…This result was consistent with the increasing trend of chain orderness in the films, indicating that charge transport in the P3HT films strongly depended on the chain-ordered structure that provided an efficient channel for charge transfer. 40 Notably, the mobility of the PTB7/P3HT blended film (with 30% P3HT) increased from 2.72 × 10 −3 to 6.76 × 10 −3 cm 2 V −1 s −1 with the application of the EEF. This mobility outperformed that of pure PTB7 (3.82 × 10 −3 cm 2 V −1 s −1 ).…”
Section: Methodsmentioning
confidence: 96%
“…This aspect appears to be particularly interesting for polar macromolecules that can become polarized with the subsequent alignment of the molecules under the electric field. In this context, it is worth emphasizing that the strong impact of the electric field was well demonstrated in the case of the phase transformation, self-ordering, 24 or self-assembling 30,31 of different materials (including polymeric ones). Here, it is worth mentioning the interesting work by Cai et al on the reversible transformation between the two-dimensional covalent organic frameworks (2D COFs) and the self-assembled molecular networks (SAMNs) of 1,3,5-tris(4-biphenyl boronic acid)benzene (TBPBA) on a graphite surface at room temperature underneath the tip of a scanning tunneling microscope (STM).…”
Section: Introductionmentioning
confidence: 96%
“…Two characteristic absorption peaks were observed at 549 and 589 nm when PBDT-TTz was dissolved in CF, which red-shifted to 553 and 595 nm, respectively, when PBDT-TTz was dissolved in CB. This red-shifting phenomenon indicated that the main chain’s conjugation length for PBDT-TTz increased in CB . According to Spano’s model, the lower energy 0–0 peak (595 nm) mainly represented π–π stacking between molecular chains or between molecular chain segments, and the higher energy 0–1 peak (553 nm) represented the intrachain state .…”
Section: Resultsmentioning
confidence: 95%
“…This red-shifting phenomenon indicated that the main chain's conjugation length for PBDT-TTz increased in CB. 44 According to Spano's model, the lower energy 0−0 peak (595 nm) mainly represented π−π stacking between molecular chains or between molecular chain segments, 45 and the higher energy 0−1 peak (553 nm) represented the intrachain state. 46 In dilute solution, molecular chains are isolated from one another with no interchain interaction.…”
Section: Polymer Chain Conformation Transformation In the Dynamic Evo...mentioning
confidence: 99%